2013
DOI: 10.7314/apjcp.2013.14.11.6411
|View full text |Cite
|
Sign up to set email alerts
|

MUTYH Association with Esophageal Adenocarcinoma in a Han Chinese Population

Abstract: Adenocarcinoma of esophagus (AE) is a complex disease, affected by a variety of genetic and environmental factors. Much evidence has shown that the MutY glycosylase homologue (MUTYH) plays a key role in the pathogenesis of many cancers. However, there have been no reports on influence on AE in the Han Chinese population. The objective of this study was to investigate this issue. A gene-based association study was conducted using three single nucleotide polymorphisms(SNPs) reported in previous studies. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Human MutY glycosylase homolog (MUTYH) is specifically involved in the removal of adenines mismatched with 8-OHdG resulting from DNA replication errors and DNA recombination [ 31 ]. Although MUTYH rs3219472 polymorphism has been identified in cholangiocarcinoma and esophageal cancer [ 17 , 18 ], there have been no reports on the MUTYH rs3219472 and rs3219493 variants and the susceptibility to bladder cancer. In the present study, we observed that MUTYH rs3219493 GG genotype and G allele had an increased risk of bladder cancer, and the finding is in consistent with the previous studies in other types of cancer [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human MutY glycosylase homolog (MUTYH) is specifically involved in the removal of adenines mismatched with 8-OHdG resulting from DNA replication errors and DNA recombination [ 31 ]. Although MUTYH rs3219472 polymorphism has been identified in cholangiocarcinoma and esophageal cancer [ 17 , 18 ], there have been no reports on the MUTYH rs3219472 and rs3219493 variants and the susceptibility to bladder cancer. In the present study, we observed that MUTYH rs3219493 GG genotype and G allele had an increased risk of bladder cancer, and the finding is in consistent with the previous studies in other types of cancer [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that multiple genes are involved in DNA damage repair systems, we ask whether there is any synergistic effects between SNPs of these genes on the risk of bladder cancer. Thus, we conducted this case-control study to investigate the associations between nineteen polymorphisms from five genes ( PARP1 , OGG1 , APEX1 , MUTYH , and XRCC1 ) of BER and two genes ( XRCC2 and XRCC3 ) of HRR, which were chosen based on the literature on other types of human cancer [ 16 18 ], and the risk of bladder cancer in Gansu Province of China.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no reports indicating a correlation of the 972G>C SNP of the MUTYH gene with the occurrence of neurodegenerative changes. However, there are a number of reports about the relationship between this polymorphism and the carcinogenesis process [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest no significant association between the two, contrasting with studies in Chinese patients reporting an association between genotype AA at this locus and elevated risk of cholangiocarcinoma, 14 as well as an association between genotype GA and decreased risk of esophageal adenocarcinoma. 15 When we examined possible joint effects of both SNPs hOGG1 rs1052133 and hMUTYH rs3219472 on the risk of NPC in our population, we found that subjects with genotype CC at hOGG1 rs1052133 and genotype AA at hMUTYH rs3219472 (CC/AA) were at significantly higher risk of NPC than those with other genotype combinations (GG/AA, GG/GG, and GG/GA). These results suggest that, at least in Asian populations, hMUTYH rs3219472 polymorphism may play a role in NPC susceptibility, just as it does in other malignancies.…”
Section: Discussionmentioning
confidence: 88%
“… 13 The hMUTYH rs3219472 SNP may influence the risk of several types of malignant tumor, such as esophageal adenocarcinoma and cholangiocarcinoma. 14 , 15 We are unaware of studies evaluating whether hMUTYH SNPs are associated with the risk of NPC.…”
Section: Introductionmentioning
confidence: 99%